Functional Analysis of the Gibberellin 2-oxidase Gene Family in Peach - Cheng, Jun; Ma, Jingjing; Zheng, Xianbo; Lv, Honglin; Zhang, Mengmeng; Tan, Bin; Ye, Xia; Wang, Wei; Zhang, Langlang; Li, Zhiqian; Li, Jidong; Feng, Jiancan (Frontiers in Plant Science, 2021)
Peach (Prunus persica [L.] Batsch] trees grow vigorously and are subject to intense pruning during orchard cultivation. Reducing the levels of endogenous gibberellins (GAs) represents an effective method for controlling branch growth. Gibberellin 2-oxidases (GA2oxs) deactivate bioactive GAs, but little is known about the GA2ox gene family in peach. In this study, we identified seven PpGA2ox genes in the peach genome, which were clustered into three subgroups: C19-GA2ox-I, C19-GA2ox-II, and C20-GA2ox-I. Overexpressing representative genes from the three subgroups, PpGA2ox-1, PpGA2ox-5, and PpGA2ox-2, in tobacco resulted in dwarf plants with shorter stems and smaller leaves than the wild type. An analysis of the GA metabolic profiles of the transgenic plants showed that PpGA2ox-5 (a member of subgroup C19-GA2ox-II) is simultaneously active against both C19-GAs and C20-GAs，which implied that C19-GA2ox-II enzymes represent intermediates of C19-GA2oxs and C20-GA2oxs. Exogenous GA3 treatment of shoot tips activated the expression of all seven PpGA2ox genes, with different response times: the C19-GA2ox genes were transcriptionally activated more rapidly than the C20-GA2ox genes. GA metabolic profile analysis suggested that C20-GA2ox depletes GA levels more broadly than C19-GA2ox. These results suggest that the PpGA2ox gene family is responsible for fine-tuning endogenous GA levels in peach. Our findings provide a theoretical basis for appropriately controlling the vigorous growth of peach trees.